MiR-613 suppresses retinoblastoma cell proliferation, invasion, and tumor formation by targeting E2F5 - Yiting Zhang; Xinyue Zhu; Xiaomin Zhu; Yan Wu; Yajun Liu; Borui Yao; Zhenping Huang (Tumor Biology, 2017)
Retinoblastoma is a common intraocular malignancy that occurs during childhood. MicroRNAs play critical roles in the regulation of retinoblastoma initiation and progression, and aberrant expression of miR-613 had been reported in various types of cancer. However, the role and mechanism of its function in retinoblastoma are still unclear. In this study, we found that miR-613 was downregulated in retinoblastoma tissues and cell lines. Overexpression of miR-613 suppressed retinoblastoma cell proliferation, migration, and invasion and induced cell cycle arrest in vitro. Additionally, overexpressed miR-613 also inhibited tumor formation of retinoblastoma cells in vivo. We further identified E2F5 as a direct target of miR-613. Reintroduction of E2F5 without 3′-untranslated region reversed the inhibitory effects of miR-613 on cell proliferation and invasion. Our data collectively indicate that miR-613 functions as a tumor suppressor in retinoblastoma through downregulating E2F5, supporting the targeting of the novel miR-613/E2F5 axis as a potentially effective therapeutic approach for retinoblastoma.